(3JShjI GdefGRYGJ GdVQjHjI Yf WQjb GdJMcje (B/ s - (3eMeO YHOGdfHj EHQGgje eUWajs; (3YHOGdMajX YHOGddg YjO s; (3eMehO eNJGQ CMeO HQjQjs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2010)
(3JfGhdJ gPg GdOQGSI WQM acQI eOj edGFeI GdJMcje chSjdI dJShjI GdefGRYGJ GdVQjHjI HGNJdGa CfhGYgG ceG JfGhdJ GdOQGSI JMdjd fUhU bGfhf GdJMcje GdeUQj Qbe (B27 (3dSfI (B1994 (3aj cd eQMdI ef eQGMd GdJMcje GdKdGK aj HGH eSJbd HOGjI ef GJaGb GdJMcje aELQGAGJ GdJMcje hGfJgGA HGdMce Gdefgj ddNUheI (B: (3hebGQfI CMcGeg eY GdCMcGe GdebGHdI GdJj JVefJgG fUhU bhGfjf GdLeGQc hGdVQGFH Ydi GdeHjYGJ (B: (3hGdVQGFH Ydj GdONd (B: (3dGSJfHGW ChLg GdNdGa hGdGJaGb HjfgG hHjGf eOj edGFeI GdJMcje dJShjI GdefGRYGJ GdVQjHjI HGNJdGa CfhGYgGs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdJLGQi, (B2010s
(3HHdjhLQGajG(B: (3UaMGJ (B269-283s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdJLGQjs; (3GdJMcje s; (3GdefGRYGJ GdVQjHjIs; (3dLGf GdWYf GdVQjHj s; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdJLGQjs